Role of Nasya Karma in Vataj Pratishyaya- A Conceptual Study - Varshney, Manish Kumar; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2023)
Pratishyaya is an Urdwajatrugata Vikara (disease above the clavicle) that can be triggered by minor etiological factors. Vataja Pratishyaya is one of the five forms of Pratishyaya mentioned in our classics and Vata is the primary dosha, with Kapha, Pitta, and Rakta as associated doshas. Vataja Pratishyaya can be correlated with Allergic Rhinitis, which is frequently encountered in OPD practise and is mostly caused by allergens and environmental pollution. Allergic Rhinitis is caused by inhalent allergens which are inhaled through nose and cause the release of freshly generated or preformed mediators. It’s an atopic disorder. Atopic dermatitis is described as a family history of sensitization to allergens in the environment (pollen, dust etc). It is a benign but chronic upper airway condition with an overall frequency of around 18% in the general population. Allergy is scientifically defined in Ayurveda under the Asatmayaj Vyadhi, while its consequences are explained in inherited, Virudhahara, Dushivish, and Ritusandhi. It occurs on a regular basis, and on attending Jeerna avastha, Nasya is the main line of treatment. It is a part of Panchakarma chikitsa and is very effective. An effort has been made in this review to examine the potentials of Nasya karma in treating Pratishaya (Allergic Rhinitis).